COMPARISON OF EFFICACY OF PHENOL AND SODIUM HYDROXIDE MATRICECTOMIES FOR MANAGEMENT OF INGROWN TOENAILS: Management of Ingrown Toenails - Arif, Abdul Jabbar; Majeed, Shahid; Arif, Ammara (Pakistan Armed Forces Medical Journal, 2015)
Objective: To compare the efficacy of Phenol and Sodium Hydroxide Matricectomies in terms of frequency of pain and wound healing in the management of Ingrown Toenails.Study Design: Randomized Clinical TrialPlace of Duration of Study: Out Patient Department of Surgery Combined Military Hospital Kharian from Aug 2010 to Feb 2011.Patients and Methods:  A total of 140 cases with Ingrown Toenails were selected and randomly divided into two groups of 70 each. Cases of Group A and B were subjected to Phenol Matricectomy (PMC) and Sodium Hydroxide Matricectomy (SHMC) respectively. Postoperative pain was comparatively and Southampton Wound Grade for wound healing were analyzed at 2nd and 10th postop day.Results: Mean age of Group A was 28.86 ± 6.423 whereas that of Group B was 28.80 ± 5.997. Group A had 58 (83%) males and 12 (17%) females. Group B had 48 (69%) males and 22 (31%) females. Postoperative pain was comparatively less in group A with statistical difference between two groups on 2nd day (p = 0.014), whereas it was less intense in group B with no statistical significant difference on 10th day (p=0.662). Wound healing was better in group B with statistical difference between two groups on 2nd (p = 0.022) and 10th day (p = 0.024). Group B (91.4%) had more statistically significant efficacy than Group A (71.4%) (p = 0.004).Conclusion: SHMC is superior to PMC in reducing pain and improving wound healing for managing Ingrown Toenails.